ANALISIS HAK WARIS ANAK ANGKAT BERDASARKAN HUKUM KEWARISAN ISLAM (STUDI KASUS PUTUSAN KASASI MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 417 K/AG/2016) - Sabrina Salmaa; Imelda Martinelli (Jurnal Hukum Adigama, 2020)
Indonesia has 3 type of inheritance Law, namely Western Inheritance law, Customary Inheritance Law, and Islamic Inheritance Law. One of Islamic Inheritance Law regulation is about the heirs after the death of the testator and its regulated in Compilation of Islamic Law. Moreover, Compilation of Islamic Law also regulate the law for adopted child. The portion for adopted child have been stipulated in in article 209 paragraph (2) Compilation of Islamic law with 1/3 and should not be more. However, the verdict that used for this study material contained inconsistencies between Supreme Court in case number 417 K/Ag/2016 decision with Islamic Inheritance Law regulation. What are the inheritance rights for adopted children based on Islamic inheritance law? Author uses normative legal research methods and interview data as supporting data. The result of the study revealed that the Supreme Court judges use another theory called argumentum per analogiam which analogies the adopted child are equalized with biological child in this inheritance cases. Moreover, the supreme court also adheres to the principle of justice adopted by Rawls where this principle prioritizes the principle of the widest possible freedom and the principle of equality of opportunity. So that the adopted child gets ½ (half) of the inheritance. It is recommended that law enforcers pay more attention to the consequences caused by changes in the position of adopted children in inheritance law, such as paying attention to the consequences that will arise on the heirs of the heirs.